Baseline overly accommodating interpersonal problems in relation to parsed alliance-outcome associations in cognitive behavioral therapy for generalized anxiety disorder. (2nd January 2023) - Constantino, Michael J.; Castonguay, Louis G.; Coyne, Alice E.; Boswell, James F.; Newman, Michelle G.
ABSTRACT : Objective: : Given its interpersonal underpinnings, relational factors may be salient in psychotherapy for generalized anxiety disorder (GAD). Supporting this point, research has indicated a positive total alliance-improvement correlation in cognitive behavioral therapy (CBT) for GAD. However, less research has disaggregated this correlation into within- and between-patient components, or examined theory-informed ways in which patient characteristics influence to these components. Thus, we first investigated parsed alliance-outcome associations in CBT for GAD. Second, consistent with theory that alliance may represent a direct interpersonal change correlate, we tested whether within -patient alliance improvements were especially therapeutic for patients with higher levels of an interpersonal problem prototypical of GAD—over accommodation. Also, consistent with theory that between -patient differences in overall alliance may be influenced by patients' preexisting relational characteristics, we tested whether more overly accommodating patients reported poorer average alliances that, in turn, related to worse outcomes. Method: : Sixty-nine patients received variants of CBT. Patients rated over accommodation at baseline, and alliance and outcome across treatment. Results: : As hypothesized, within-patient alliance improvements correlated with subsequent anxiety reduction, and this association was stronger for more overly accommodating patients. All between-patient associations were nonsignificant. Conclusion: : Results help clarify the nuanced role of alliance in CBT for GAD.